PENENTUAN LOKASI GUDANG PUSAT PENYALUR LOGISTIK DAN PERALATAN PENANGGULANGAN BENCANA DENGAN MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS - ASEP ADANG SUPRIYADI; DEBBIE KEMALA SARI; KAREL L. MANDAGIE (JURNAL TEKNIK INDUSTRI, 2018)
Indonesia retains high level of vulnerability to natural disasters caused by its dynamic geological (plate) condition. Disaster management efforts in as seen from the performance of the apparatus and institutional disaster management and disaster risk awareness are still low. Organizing and well-planned management is highly needed, thereforethat disasters would not cause prolonged impact. This requires creative and innovative thinking associated with the presence of disaster management logistics warehouse. The aim of this study is to determine the location and to design the layout of the central warehouse distributor logistics and disaster response equipment in Halim Air Force Base, East Jakarta. Geographic Information Systems approach will be use in determining strategic location as the central warehouse distributor of disaster. The variables that significantly influence the determination of the location of the central warehouse distributor logistics and disaster response equipment are: the distance to the main roads, the distance to the apron, the distance to the taxiways and the land use as vacant land. These variables are not obtained through direct measurements in the field, but by utilizing aerial photo map. The assessment process of land on the aerial photographic map is using scoring methods and overlaying maps techniques with ArcGIS 10 application. The layout design of the logistics and disaster response equipment warehouse from land assessment results, are based on a simple straight line method with some modifications. The results of this research is a map of location of the central distributor logistics and disaster response equipment warehouse in the western part of Indonesia, namely at Halim Air Force Base at the coordinate of 106º53'47 "BT 6º15'10" LS. The ideal total value derived from the result of calculation of location is about 23 with an area of 17 528 m². The analysis for the shortest route to the location of the warehouse is done by network analysis method. Based on the obtain of the land area extent, the recommended numbers of central distributors warehouse in the context of disaster management are two, which are special logistics warehouse and specialized equipment warehouse.Keywords: Aerial Map, Geographic Information Systems, Simple Straight Line Method